Combination Therapy With Anti-PD-1 or PD-1 Antibody Alone in Asian Pediatric Patients With Relapsed or Refractory Cancer - Que, Yi; Wang, Juan; Zhu, Jia; Li, Na; Huang, Junting; Lu, Suying; Sun, Feifei; Zhang, Lian; Zhen, Zijun; Zhang, Li; Cai, Ruiqing; Guo, Haixia; et al. (Frontiers in Immunology, 2021)
There is limited experience of PD-1 antibody combined with other therapies in children. We aimed to explore the antitumor activity and safety of PD-1 antibody monotherapy or combination with other regimens in relapsed or refractory pediatric cancer. This is a retrospective-case study conducted in two Chinese expert centers. The primary objective of this study was to describe the overall response rate (ORR) and disease control rate (DCR). Secondary objectives included characterizing toxicities. Of the 22 pediatric patients with cancer who received PD-1 inhibitors, the median follow-up for all patients after the commencement of PD-1 therapy with or without other regimens was 12.3 months (0 - 43 months). PD-1 antibody monotherapy demonstrated antitumor activity in a population of pediatric patients with Hodgkin lymphoma (HL), with an objective response rate (ORR) and disease control rate (DCR) of 83.3% (3CR and 2PR) and 100%, respectively. However, no objective response was observed in patients with melanoma or Burkitt lymphoma evaluated in this study. We reviewed responses for patients with chemotherapy, decitabine or everolimus combination therapies with PD-1 antibodies, and found that PD-1 antibody combined with decitabine showed potential efficacy in pediatric patients with advanced embryonal rhabdomyosarcoma and lymphoepitheliomatoid-like carcinoma. There were no severe treatment-related adverse events (TRAEs) directly attributed to PD-1 antibody monotherapy in Asian pediatric patients with lower incidence of hematologic toxicity and nonhematologic toxicity. The Grade ≥3 TRAEs were attributed to the combination chemotherapy.